2003
DOI: 10.1189/jlb.0303101
|View full text |Cite
|
Sign up to set email alerts
|

The cannabinoid system and immune modulation

Abstract: Studies on the effects of marijuana smoking have evolved into the discovery and description of the endocannabinoid system. To date, this system is composed of two receptors, CB1 and CB2, and endogenous ligands including anandamide, 2-arachidonoyl glycerol, and others. CB1 receptors and ligands are found in the brain as well as immune and other peripheral tissues. Conversely, CB2 receptors and ligands are found primarily in the periphery, especially in immune cells. Cannabinoid receptors are G protein-coupled r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
409
2
8

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 460 publications
(421 citation statements)
references
References 104 publications
2
409
2
8
Order By: Relevance
“…Although both receptors have a role to restore homeostasis mechanisms, CB1 receptors perform their function mainly in the CNS, whereas CB2 receptors do it mainly at the peripheral level. Some authors have reported CB1 expression in human PBMCs, but its levels are much lower than CB2 and considerable work is still needed to define its relevance and regulatory mechanism/s (Klein et al, 2003). Second, 81.1% of the patients were receiving antipsychotic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Although both receptors have a role to restore homeostasis mechanisms, CB1 receptors perform their function mainly in the CNS, whereas CB2 receptors do it mainly at the peripheral level. Some authors have reported CB1 expression in human PBMCs, but its levels are much lower than CB2 and considerable work is still needed to define its relevance and regulatory mechanism/s (Klein et al, 2003). Second, 81.1% of the patients were receiving antipsychotic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In human peripheral blood cells, CB 1 receptor mRNA and protein are expressed, in decreasing rank order, by B cells, NK cells, neutrophils, CD8 ĂŸ T cells, monocytes, and CD4 ĂŸ T cells (Galiegue et al, 1995). CB 1 and CB 2 receptors are expressed by human peripheral blood cell-derived dendritic cells (DCs) (Matias et al, 2002), and mRNA for both CB 1 and CB 2 receptors is expressed in mouse bone marrow-derived DC (Klein et al, 2003). Mouse peritoneal macrophages and rodent macrophage cell lines express CB 2 receptor mRNA, and this message is more abundant than the message for CB 1 (Carlisle et al, 2002).…”
Section: Peripheral Immune Cells Express Cannabinoid Receptorsmentioning
confidence: 99%
“…It is generally believed that cannabinoids alter the immune functions through their ability to mediate an effect on cytokine production and to exert anti-proliferative properties [15] (Review). Recent studies from our laboratory suggested that the anti-proliferative activity of THC may result from its ability to trigger apoptosis in immune cells [16].…”
Section: Introductionmentioning
confidence: 99%